PENGEMBANGAN PARIWISATA KAWASAN GUNUNG WAYANG DAN SEKITARNYA - -, Ildrem Syafri (Bulletin of Scientific Contribution, 2009)
The southern part of Bandung area available some geo-tourism, both was developed or not yet. Wayang Mount area and surrounding are one another that fully developed not yet. That area has geological phenomena and natural preserve. The objective of research is supporting geological information available for tourism developing at Wayang Mount area and surrounding. Main theme of research is modeling of tourism development that cares with environment. Base on literatures study, Bandung area has potency and constraint in connection with area development. That two aspects cause environmental problem that necessary integrated management. Some methods are used to get data; among other are literature study, field survey, and laboratory analysis. Probabilistic approach is used for data analysis.Research result show Wayang Mount area and surrounding is product of Quaternary volcanic. It has gentle to very steeply with elevation about from 1,425 to 2,198 meters from sea level. The drainage patterns are sub-radier, sub-dendritic, sub-parallel, and sub-rectangular. Stream order from 1 to 5 with drainage density reach 8.3 km / square km. Lithology is product of earlier Pleistocene to Holocene volcanic. That lithology consist volcanic breccia, tuff, and lava. A part of them hydrothermal altered and weathered. Base on analysis of microscopic, geochemistry and physic-mechanic show rock and weathering result’s can studied with measured. The available of hot spring in Wayang Mount area is controlled by structure pattern and active tectonic.The tourism development at Wayang Mount and vicinity is supported by strategic location, some geological phenomena, exquisite view, etc. That area is suitable for geo-tourism and agro-tourism development. The constraint aspect in development program is complicated environmental problem. Those problems are Wayang Mount area is natural preserve and main water resource of Citarum River.